2003
DOI: 10.1002/asi.10299
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of youngsters' use of CD‐ROM and the Internet as information resources

Abstract: Little research has compared youngsters' use of CD-ROM and the Internet for information-seeking purposes. Nevertheless, the area has recently been addressed within a largely qualitative project more generally devoted to young people's information universes. Home access to the Internet was seen to be more limited than that to CD-ROM, although the former was consulted to tackle needs of a greater number of types. The strategies employed to exploit each form of information resource were essentially similar. No at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Almost no work has been undertaken to compare young people's information seeking on the Web with any of these other technologies, although the sixthgrade students in Large and Beheshti's (2000) study did comment briefly on CD-ROMs as an alternative to the Web as a source of information for school projects. In contrast, Hirsh (1999) included print and CD-ROM as well as the Web in her investigation of information evaluation by elementary school students, and Shenton and Dixon (2003) compared students' use of CD-ROM and the Web as information resources. Shenton and Dixon found that the search strategies adopted were similar for both technologies.…”
Section: Information-seeking Studiesmentioning
confidence: 90%
“…Almost no work has been undertaken to compare young people's information seeking on the Web with any of these other technologies, although the sixthgrade students in Large and Beheshti's (2000) study did comment briefly on CD-ROMs as an alternative to the Web as a source of information for school projects. In contrast, Hirsh (1999) included print and CD-ROM as well as the Web in her investigation of information evaluation by elementary school students, and Shenton and Dixon (2003) compared students' use of CD-ROM and the Web as information resources. Shenton and Dixon found that the search strategies adopted were similar for both technologies.…”
Section: Information-seeking Studiesmentioning
confidence: 90%
“…From this literature investigators have focused on the cognitive behavior and alluded to one or two affective factors expressed by users such as preferences, satisfaction, frustration, and joy (Bilal & Wang, 2005;Shenton & Dixon, 2003;Large & Beheshti, 2000;Sullivan, Norris, Peet, & Soloway, 2000;Hirsh, 1999;Kafai & Bates, 1997). According to Picard (1997), common factors that computer users experience include confusion, frustration, dislike, like, joy, satisfaction, motivation, and preference.…”
Section: The Status Of Researchmentioning
confidence: 99%
“…Retrieval requires an intersection of metadata used within the system and the user's search terms. Information-seeking research has uncovered representation obstacles such as spelling errors, misuse of search features, diffi culty in selection of initial and alternate search terms, and the inappropriate nature of the system's controlled vocabulary (Moore & St. George, 1991;Solomon, 1993;Borgman, Hirsch, Walter, & Gallagher, 1995;Hirsh, 1997;Bilal, 2000aBilal, , 2000bShenton & Dixon, 2003;Abbas, 2001). Other research links children's cognitive and developmental abilities to issues of retrieval as well as system design (Cooper, 2002;Bilal, 2000aBilal, , 2000bBorgman, Hirsch, Walter, & Gallagher, 1995;Hirsh, 1997).…”
Section: Representation Issues In Information Seekingmentioning
confidence: 99%